Factors Associated With Newly HIV Infection and Transmitted Drug Resistance Among Men Who Have Sex With Men in Harbin, P.R. China - Hui, Shan; Chen, Fangfang; Li, Yi; Cui, Yan; Zhang, Jinhui; Zhang, Ling; Yang, Yisi; Liu, Yanlin; Zhao, Yashuang; Lv, Fan (Frontiers in Public Health, 2022)
Background This study aimed to evaluate HIV incidence, factors associated with HIV incidence and transmitted drug resistance (TDR) among newly infected men who have sex with men (MSM) in Harbin, P.R. China. Methods A cohort study was conducted among MSM in Harbin during 2013 and 2018, with a follow-up frequency of every 6 months. Blood samples from MSM were tested for HIV antibodies, RNA was extracted from plasma, and the pol gene was sequenced, and genotypic drug-resistance analyses were performed. Results From 2013 to 2018, the overall rate of HIV incidence was 3.55/100 PY. Syphilis infection, unprotected sex with men in the past 6 months, and unawareness of HIV/AIDS knowledge were risk factors for HIV seroconversion. The distribution of HIV genotypes was as follows: CRF01_AE, 57.1%; CRF07_BC, 28.5%; CRF55_01B, 2.0%; B, 8.2%. The prevalence of transmitted drug resistance was 4.08%. Conclusion HIV incidence in MSM in Harbin is moderately high, and transmitted drug resistance exists in the population.